Does Social Support Predicts a Person's Quality of Life? - Onn, P. P.; Teoh, H. J.; Sinniah, D.; Pillay, S. K.; Kannan, K. (Faculty of Psychology, Universitas Surabaya, 2006)
The purpose of this study is to examine whether social support predicts a person's quality of life. Seventynine adults between the ages of 18 to 55 year-old participated in this study. Subjects were required to complete 2 sets of questionnaires consisting of